1997
DOI: 10.1007/s004380050343
|View full text |Cite
|
Sign up to set email alerts
|

Tomato chromosome 1: high resolution genetic and physical mapping of the short arm in an interspecific Lycopersicon esculentum×L. peruvianum cross

Abstract: A detailed map of part of the short arm of chromosome 1 proximal to the Cf-4/Cf-9 gene cluster was generated by using an F2 population of 314 plants obtained from the cross between the remotely related species Lycopersicon esculentum and L. peruvianum. Six markers that cosegregate in an L. esculentum x L. pennellii F2 population showed high recombination frequencies in the present interspecific population, spanning an interval of approximately 13 cM. Physical distances between RFLP markers were estimated by pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…The observation that in two out of the three deletions a Cf-4 homologous sequence outside the introgressed region was also missing, fits with the observation of intergenic recombination with 'Cf-4' homologous sequences, mapping proximal or distal to the introgressed Cf-4 L. hirsutum cluster. The presence of these clusters proximal and distal to Cf-4 was indeed observed by Bonnema et al (1997) and Parniske et al (1997). Also, the relatively high frequency by which these mutants were found (3 in 20 000; 1.5 ϫ 10 -4 ) is comparable with the reported frequencies for the Rp1-J (5.1 ϫ 10 -4 ) and Rp1-G (3.2 ϫ 10 -3 ) resistance genes (Sudapak et al, 1993).…”
Section: Analysis Of Mutants With a Genomic Deletionsupporting
confidence: 59%
See 1 more Smart Citation
“…The observation that in two out of the three deletions a Cf-4 homologous sequence outside the introgressed region was also missing, fits with the observation of intergenic recombination with 'Cf-4' homologous sequences, mapping proximal or distal to the introgressed Cf-4 L. hirsutum cluster. The presence of these clusters proximal and distal to Cf-4 was indeed observed by Bonnema et al (1997) and Parniske et al (1997). Also, the relatively high frequency by which these mutants were found (3 in 20 000; 1.5 ϫ 10 -4 ) is comparable with the reported frequencies for the Rp1-J (5.1 ϫ 10 -4 ) and Rp1-G (3.2 ϫ 10 -3 ) resistance genes (Sudapak et al, 1993).…”
Section: Analysis Of Mutants With a Genomic Deletionsupporting
confidence: 59%
“…In previous studies, the Cf-4 resistance gene has been mapped between the markers CP46 and TG236 (Figure 4) Bonnema et al, 1997). The L. hirsutum-introgressed region in L. esculentum cv.…”
Section: Molecular Characterization Of the Stable Mutantsmentioning
confidence: 99%
“…Different authors observed that recombination rate, which determines the fragment sizes, depends not only on the species but also on the region of the genome considered. Bonnema et al (1997) compared recombination rates in an F2 population obtained from a cross between tomato and S. peruvianum, with recombination rates of the F2 population derived from S. pennellii LA716 (Tanksley et al 1992). They observed that recombination was reduced at chromosome 2 and 5, while at chromosomes 1, 7, 9, 10 and 11 recombination rates were higher.…”
Section: Discussionmentioning
confidence: 99%
“…The entire library consisted of 2.7 · 10 5 clones in 180 pools representing 5.6 haploid genome equivalents based on an average insert size of 20 kb. Cosmid pools were screened by PCR with primers of the CT116 CAPS marker (Bonnema et al 1997) and with degenerate primers which amplify LRR 1 to 17 of Hcr9s (HCR9C1F: 5¢-catgggatggmrttsattgtgac-3¢ and HCR9C1R: 5¢-catwgtgggattgtyccctcc-3¢). Pools that yielded a PCR product were selected.…”
Section: Experimental Procedures Pcld04541 Binary Cosmid Library Consmentioning
confidence: 99%
“…Bonnema et al (1997) showed by using a cross between L. esculentum and L. peruvianum LA2157, that near the CT116 locus a genetic distance of 1 cM corresponds to a physical distance of maximally 52 kb. The tight linkage of Cf-Ecp2 with CT116 and the cosegregation with Hcr9s prompted us to use a combination of a homologybased-and map-based cloning approach to characterise the OR Hcr9 gene cluster and to identify candidate Cf-Ecp2 genes.…”
Section: Introductionmentioning
confidence: 99%